2006
DOI: 10.1529/biophysj.106.085548
|View full text |Cite|
|
Sign up to set email alerts
|

First-Principles Transversal DNA Conductance Deconstructed

Abstract: First-principles calculation of the transverse conductance across DNA fragments placed between gold nanoelectrodes reveals that such conductance describes electron tunneling that depends critically on geometrical rather than electronic-structure properties. By factoring the first-principles result into two simple and approximately independent tunneling factors, we show that the conductances of the A, C, G, and T fragments differ only because of their sizes: the larger is the DNA base, the smaller its distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 17 publications
0
68
0
Order By: Relevance
“…They concluded that sequencing should be possible and also investigated the effect of water and other environmental factors including dynamics, as well as tunnelling noise characteristics on the device performance 80,81 . Fuentes-Cabrera and coworkers 82,83 stressed that in off-resonant tunnelling regime dynamic effects, such as Brownian motion and the exact geometry of the DNA in the junction, may dominate the tunnelling current, rather than base-specific electronic factors. In essence, however, it has become clear that motion of DNA in the tunnelling junction and in particular the DNA/electrode interaction would have to be controlled carefully to make sequencing-by-tunnelling in nanopore configuration a reality.…”
Section: Small-molecule Sensing By Tunnelling Currentsmentioning
confidence: 99%
“…They concluded that sequencing should be possible and also investigated the effect of water and other environmental factors including dynamics, as well as tunnelling noise characteristics on the device performance 80,81 . Fuentes-Cabrera and coworkers 82,83 stressed that in off-resonant tunnelling regime dynamic effects, such as Brownian motion and the exact geometry of the DNA in the junction, may dominate the tunnelling current, rather than base-specific electronic factors. In essence, however, it has become clear that motion of DNA in the tunnelling junction and in particular the DNA/electrode interaction would have to be controlled carefully to make sequencing-by-tunnelling in nanopore configuration a reality.…”
Section: Small-molecule Sensing By Tunnelling Currentsmentioning
confidence: 99%
“…52 As an alternative, the layout proposed here can also be used to directly detect voltage fluctuations due to the local and unique dipole moments of the bases. 53,54 This capacitive detection approach is not preferred, however, due to its reliance on the relatively long-range capacitive interaction, possibly limiting the spatial resolution with which individual bases can be resolved.…”
mentioning
confidence: 99%
“…13 On the theoretical front, the transverse tunneling conductance across nucleobases placed between two gold electrodes has been actively investigated and debated. 4,7,[16][17][18][19][20][21] Interestingly, recently some special attention has been dedicated to exploring graphene nanopore, graphene nanoribbon and carbon nanotubes (CNT) as potential electrodes materials. [22][23][24] Despite these many works, a key question still remains largely unanswered, namely, how can one enhance the nucleotide-electrode interaction to a point where the transmigration is still possible, but the geometrical fluctuations are sufficiently suppressed to allow unambiguous single nucleotide recognition.…”
Section: Introductionmentioning
confidence: 99%